A novel in situ transesterification of yellow horn seeds to biodiesel using a dual function switchable solvent. (15th March 2022) - Zhang, Su; Wang, Litao; Wang, Jiandong; Yang, Jie; Fu, Lina; Cai, Zihui; Fu, Yujie
Graphical abstract: Highlights: Switchable solvents were used for biodiesel production as both a green solvent and reusable catalyst. Simultaneous oil extraction and biodiesel production from yellow horn seeds was achieved. The recyclability of the switchable solvent used for biodiesel production was evaluated. Molecular dynamics simulation was developed to analyze the mechanism of DMCHA assisted direct transesterification. Abstract: A novel and cyclic in situ transesterification of yellow horn ( Xanthoceras sorbifolia Bunge.) seeds to biodiesel using the switchable solvent, N, N -dimethylcyclohexylamine (DMCHA) as both a reusable solvent and catalyst was proposed. An optimizing study for the reaction conditions has been performed through response surface methodology. The maximum yield of fatty acid methyl esters (FAMEs) achieved 96.07% under the best conditions of temperature 63.93 °C, 28.05 min, methanol amount of 10.41 mL/g (v/w of material) and DMCHA amount of 16.42 mL/g. Notably, The results of mechanism study combined with molecular dynamics and quantum chemistry theory showed that DMCHA is compatible with the triglycerides, and the effect of the hydrogen bonds, interaction energy, and radial distribution function on DMCHA performance were investigated for the first time. This new configuration of using switchable solvent for simultaneous extraction and reaction would be an appropriate, efficient and environment-friendly approach for simplify biodiesel production.